Beginning JavaFX - PremKumar, Lawrence; Mohan, Praveen (New York : Apress L. P., 2010)
Annotation The open source JavaFX platform offers a Java-based approach to rich Internet application (RIA) development$1 (Ban alternative to Adobe Flash/Flex and Microsoft Silverlight. At over 100 million downloads, JavaFX is poised to be a significant player.Written by a JavaFX engineer and developer, this book is one of the first on the JavaFX platform to give you the following:The fundamentals of JavaFX scripting on desktop and mobile platformsExamples of RIAs using JavaFX GraphicsMedia and animation using JavaFXSee how JavaFX gives you dynamic Java effects in your RIA development.What you$1 (Bll learnHow to use the JavaFX scripting language, beginning with a simple (3z(BHello, World(3y (BapplicationHow to use JavaFX data types, operators, expressions, functions, sequences, bindings, triggers, and moreHow to work with the JavaFX classes, packages, exception handling, inheritance, and moreHow to use JavaFX GraphicsHow to work with JavaFX animationHow to create a working RIA using JavaFXWho this book is forThis book is for Flash, Silverlight, and other RIA developers looking to use and integrate JavaFX in their Java RIA applications, whether it$1 (Bs for the desktop or mobile environments. This book is also for those new to RIA development.Table of ContentsIntroduction to RIAIntroduction to JavaFXData TypesOperators and ExpressionsFunctionsClass DefinitionsAccess SpecifiersInheritanceData BindingSequencesTriggersIntroduction to JavaFX UI ElementsIntroduction to Animations